Mixed Spacer Cation Stabilization of Blue‐Emitting n = 2 Ruddlesden–Popper Organic–Inorganic Halide Perovskite Films - Leung, Tik Lun; Tam, Ho Won; Liu, Fangzhou; Lin, Jingyang; Ng, Alan Man Ching; Chan, Wai Kin; Chen, Wei; He, Zhubing; Lončarić, Ivor; Grisanti, Luca; Ma, Chao; Wong, Kam Sing; et al. (Advanced optical materials, 2020)
Ruddlesden–Popper halide perovskite (RPP) materials are of significant interest for light‐emitting devices since their emission wavelength can be controlled by tuning the number of layers n, resulting in improved spectral stability compared to mixed halide devices. However, RPP films typically contain phases with different n, and the low n phases tend to be unstable upon exposure to humidity, irradiation, and/or elevated temperature which hinders the achievement of pure blue emission from n = 2 films. In this work, two spacer cations are used to form an RPP film with mixed cation bilayer and high n = 2 phase purity, improved stability, and brighter light emission compared to a single spacer cation RPP. The stabilization of n = 2 phase is attributed to favorable formation energy, reduced strain, and reduced electron–phonon coupling compared to the RPP films with only one type of spacer cation. Using this approach, pure blue light‐emitting diodes (LEDs) with Commission Internationale de l'éclairage (CIE) coordinates of (0.156, 0.088) and excellent spectral stability are achieved. Ruddlesden–Popper halide perovskite (RPP) materials are promising candidates for light‐emitting devices with tunable emission wavelength. However, pure blue emission n = 2 RPP films are unstable for light‐emitting diode (LED) applications. The stabilization of n = 2 phase is demonstrated by employing two spacer cations to form a mixed cation bilayer structure. Pure blue LEDs are achieved with excellent spectral stability.